Indoor exposure levels of bacteria and fungi in residences, schools, and offices in China: A systematic review. (25th September 2020) - Guo, Kangqi; Qian, Hua; Zhao, Dongliang; Ye, Jin; Zhang, Yinping; Kan, Haidong; Zhao, Zhuohui; Deng, Furong; Huang, Chen; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; et al.
Abstract: Microbes in buildings have attracted extensive attention from both the research community and the general public due to their close relationship with human health. However, there still lacks comprehensive information on the indoor exposure level of microbes in China. This study systematically reviews exposure levels, the community structures, and the impact factors of airborne bacteria and fungi in residences, schools, and offices in China. We reviewed the major literature databases between 1980 and 2019 and selected 55 original studies based on a set of criteria. Results show that the concentration of indoor bacteria varies from 72.5 to 7500 CFU/m 3, with a median value of 1000 CFU/m 3, and the concentration of fungi varies from 12 to 9730 CFU/m 3, with a median value of 526 CFU/m 3 . The concentration level of microbes varies in different climate zones, with higher bacterial concentrations in the severe cold zone, and higher fungal concentrations in the hot summer and warm winter zone. Among different buildings, classrooms have the highest average bacteria and fungi levels. This review reveals that a unified assessment system based on health effects is needed for evaluating the exposure levels of bacteria and fungi.